Millimetre wave antennas for gigabit wireless communications : a practical guide to design and analysis in a system context - 438964 Huang, Kao-Cheng; Edwards, David J. (Chichester, West Sussex, England ; Hoboken, NJ, USA : Wiley, 2008)
16